Restrukturyzacja i co dalej? - kształtowanie strategii szpitala na podstawie doświadczeń francuskich - Karniej, Piotr (Creation of Hospital Strategy Based on French Experience, 2006)
In the process of managing an enterprise, a range of methods for making strategic decisions are applied. Because each organisation has to plan its activity several years in advance, and market mechanisms are moving into health care, it seems appropriate to use tools for applied strategic analysis in enterprises to evaluate hospital strategy. Because of the necessity of limiting the risk associated with conducting activity - in this case medical activity - based on predicting situations that could arise, each organisation must plan for the long term. In this work, we find out about the need for shaping a medical organisation's strategic position on the strength of, among others, foreign experience. Because France is a completely different country to Poland in terms of financing health care, and similar in its structure of providing medical services, it is possible to make the assumption that the difficulties that we can see at present in the organisation of the health service in France will also exist in Poland after the stabilisation of the system of financing and the functioning of medical care. We should therefore prepare today for expected difficulties and take them into account when creating a strategy for Polish health care facilities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 43-51